2021
DOI: 10.1186/s12891-021-04402-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surgical site infection on patients’ outcome after fixation of tibial plateau fractures: a retrospective multicenter study

Abstract: Background Surgical site infection (SSI) occurs in 3–10 % of patients with surgically treated tibial plateau fractures. This study aimed to evaluate the impact of SSI on patients’ outcome after fixation of tibial plateau fractures. Methods We conducted a retrospective multicenter study in seven participating level I trauma centers between January 2005 and December 2014. All participating centers followed up with patients with SSI. In addition, thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…An important difference between these studies and our series is that we used a dual incision approach with double plating in 52% of patients (compared to Jansen et al: 14% [ 26 ], Henkelmann. : 14% [ 27 ], Timmers et al: 3% [ 29 ]), which might explain the difference in scores: bivariate analysis in our series demonstrated that patients with bicondylar fractures (and consequently dual incision treatment) reported significantly lower functional outcomes. Another factor that might influence these results is indication bias; we only used HCS for fractures with comminuted, small, and intra-articular fragments in which reduction with standard implants was deemed insufficient.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…An important difference between these studies and our series is that we used a dual incision approach with double plating in 52% of patients (compared to Jansen et al: 14% [ 26 ], Henkelmann. : 14% [ 27 ], Timmers et al: 3% [ 29 ]), which might explain the difference in scores: bivariate analysis in our series demonstrated that patients with bicondylar fractures (and consequently dual incision treatment) reported significantly lower functional outcomes. Another factor that might influence these results is indication bias; we only used HCS for fractures with comminuted, small, and intra-articular fragments in which reduction with standard implants was deemed insufficient.…”
Section: Discussionmentioning
confidence: 60%
“…They report a mean KOOS score of 68 points (our series median: 60 points). Henkelmann et al evaluated 246 patients with a AO type B and C tibial plateau fractures (without post-operative SSI) after a mean follow-up of 78.9 months [ 27 ]. They report mean KOOS subscores for pain of 75 (our series median: 71), symptoms and stiffness 75 (our series median: 69), ADL 81 (our series median: 85), sports 41 (our series median: 30), and QOL 56 (our series median: 34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is typically placed through a posteromedial incision and secured to the bone using screws or other fixation devices. The plate is contoured to fit the shape of the bone and is designed to resist the forces that would otherwise cause the fracture to shift or collapse (19) .…”
Section: Discussionmentioning
confidence: 99%
“…The best estimate I could find of the risk of a devastating surgical site infection after open reduction internal fixation (ORIF) of tibial plateau fractures is about 5% [4], and based on that study's design, it's certain that infections occur even more frequently than that. Patients who develop infections can expect persistent pain and severely impaired function; both in that study [4] and comparing outcomes scores in that study to those in this month's CORR ® article [12], we see that infection reduces Knee Injury and Osteoarthritis Outcome Scores (KOOS) by about 30% to 40%. And not surprisingly, TKAs performed in patients with infection after ORIF of the tibial plateau are much more likely to develop periprosthetic joint infection after the arthroplasty [6].…”
mentioning
confidence: 99%